Generalized Dermatitis in Clinical Practice - Nedorost, Susan T. (Springer London : Imprint: Springer, 2012)
Generalized dermatitis  is often chronic and debilitating. Many cases are multifactorial, which makes diagnosis and targeted treatment difficult. Although a very common reason for presentation to both dermatologists and primary care physicians, many practitioners fail to control symptoms adequately. Generalized Dermatitis in Clinical Practice summarizes the diagnostic and management options of this complex, multifactorial, and often chronic disease. Distilling a wealth of clinical insight, the author reviews the pathophysiology and differential diagnosis in the context of patient management. This concise clinical reference is an ideal way for dermatologists, allergists, and primary care physicians to approach the patient suffering from widespread dermatitis.